2021
DOI: 10.1155/2021/9991001
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Crosstalk between Ferroptosis and Necroptosis: Novel Therapeutics in Ischemic Stroke

Abstract: Ferroptosis is a nonapoptotic form of cell death characterized by iron-dependent accumulation of lipid hydroperoxides to lethal levels. Necroptosis, an alternative form of programmed necrosis, is regulated by receptor-interacting protein (RIP) 1 activation and by RIP3 and mixed-lineage kinase domain-like (MLKL) phosphorylation. Ferroptosis and necroptosis both play important roles in the pathological progress in ischemic stroke, which is a complex brain disease regulated by several cell death pathways. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 204 publications
(312 reference statements)
2
53
0
Order By: Relevance
“…That means ferroptosis still occurs frequently in recent necroptosis studies, indicating that the cross-talk between necroptosis and ferroptosis might be a new rising research area. Multiple structural, functional, and mechanistic evidence proved their cross-talk ( 60 ). One of the mechanisms of ferroptosis is that iron overload leads to a mitochondrial permeability transition pore (MPTP) opening, which exacerbates RIPK1 phosphorylation and contributes to necroptosis ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…That means ferroptosis still occurs frequently in recent necroptosis studies, indicating that the cross-talk between necroptosis and ferroptosis might be a new rising research area. Multiple structural, functional, and mechanistic evidence proved their cross-talk ( 60 ). One of the mechanisms of ferroptosis is that iron overload leads to a mitochondrial permeability transition pore (MPTP) opening, which exacerbates RIPK1 phosphorylation and contributes to necroptosis ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell death, especially apoptosis, has been demonstrated as a hallmark after SAH during the past few decades [ 6 , 7 ]. Ferroptosis, characterized by iron-dependent lipid peroxidation, is a new form of programmed cell death, which differs from apoptosis or necroptosis [ 8 , 9 ]. The morphological features of a ferroptotic cell are shrunken mitochondria with increased mitochondrial membrane density, a reduction of mitochondria crista, and outer membrane rupture [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein 90 (HSP90) is defined as a common regulatory nodal between ferroptosis and necroptosis ( Wu et al, 2019 ). Friedmann Angeli et al demonstrated that necrostatin-1 (RIP1 inhibitor) inhibits ferroptosis through a necroptosis/RIP1-independent manner, but ferroptosis inhibitors cannot inhibit necroptosis ( Friedmann Angeli et al, 2014 ) and the specific link between ferroptosis and necroptosis remains to be clarified after stroke ( Zille et al, 2017 ; Zhou et al, 2021 ). Carthamin yellow attenuates cerebral I/R injury via suppressing NF-κB/NLRP3-mediated pyroptosis and ACSL4-mediated ferroptosis in rats ( Guo et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%